Selected Topics on Business Informatics: Editorial Introduction to Issue 29 of CSIMQ - Birger Lantow; Erika Nazaruka; Kurt Sandkuhl (Complex Systems Informatics and Modeling Quarterly)
The objective of this thematic issue was to show the diversity of research in the field of business informatics, both from the perspective of application areas and from the research methodologies applied. Application areas visible in this issue are product development in manufacturing industries, online learning in universities, innovation activities in networks of museums, and curriculum engineering in educational organizations. Research methods include various quantitative and qualitative approaches combined with prototyping and the design science paradigm.